Tropospheric carbon monoxide concentrations and variability on Venus from Venus Express/VIRTIS-M observations - Tsang, C; Irwin, P; Wilson, C; Taylor, F; Lee, C; de Kok, R; Drossart, P; Piccioni, G; Bezard, B; Calcutt, S (American Geophysical Union, 2008)
We present nightside observations of tropospheric carbon monoxide in the southern hemisphere near the 35 km height level, the first from Venus Express/Visible and Infrared Thermal Imaging Spectrometer (VIRTIS)-M-IR. VIRTIS-M data from 2.18 to 2.50 μm, with a spectral resolution of 10 nm, were used in the analysis. Spectra were binned, with widths ranging from 5 to 30 spatial pixels, to increase the signal-to-noise ratio, while at the same time reducing the total number of retrievals required for complete spatial coverage. We calculate the mean abundance for carbon monoxide at the equator to be 23 ± 2 ppm. This 40% equator-to-pole increase is consistent with the values found by Collard et al, (1993) from Galileo/NIMS observations. Observations suggest an overturning in this CO gradient past 60°S, declining to abundances seen in the midlatitudes. Zonal variability in this peak value has also been measured, varying on the order of 10% (~3 ppm) at different longitudes on a latitude circle. The zonal variability of the CO abundance has possible implications for the lifetime of CO and its dynamics in the troposphere. This work has definitively established a distribution of tropospheric CO, which is consistent with a Hadley cell circulation, and placed limits on the latitudinal extent of the cell.